Associations of unilateral whisker and olfactory signals induce synapse formation and memory cell recruitment in bilateral barrel cortices: cellular mechanism for unilateral training toward bilateral memory - Zilong Gao; Zilong Gao; Lei Chen; Ruicheng Fan; Wei Lu; Dangui Wang; Shan Cui; Li Huang; Shidi Zhao; Sudong Guan; Yan Zhu; Jin-Hui Wang; et al. (Frontiers in Cellular Neuroscience, 2016)
Somatosensory signals and operative skills learned by unilateral limbs can be retrieved bilaterally. In terms of cellular mechanism underlying this unilateral learning toward bilateral memory, we hypothesized that associative memory cells in bilateral cortices and synapse innervations between them were produced. In the examination of this hypothesis, we have observed that paired unilateral whisker and odor stimulations led to odorant-induced whisker motions in bilateral sides, which were attenuated by inhibiting the activity of barrel cortices. In the mice that showed bilateral cross-modal responses, the neurons in both sides of barrel cortices became to encode this new odor signal alongside the innate whisker signal. Axon projections and synapse formations from the barrel cortex, which was co-activated with the piriform cortex, toward its contralateral barrel cortex were upregulated. Glutamatergic synaptic transmission in bilateral barrel cortices was upregulated and GABAergic synaptic transmission was downregulated. The associative activations of the sensory cortices facilitate new axon projection, glutamatergic synapse formation and GABAergic synapse downregulation, which drive the neurons to be recruited as associative memory cells in the bilateral cortices. Our data reveals the productions of associative memory cells and synapse innervations in bilateral sensory cortices for unilateral training toward bilateral memory.